Light Intensity Promote Pigment Contents, Biomass Production, Total Lipid and Specific Fatty Acid Profile on Nannochloropsis sp. Culture - Ervia Yudiati; Alifia Nabilla Putri; Akbar Harahap; Nuril Azhar; Chrisna Adi Suryono; Danang Ambar Prabowo; Rabia Alghazeer (Marine Science Department Diponegoro University, 2022)
Nannochloropsis sp is marine microalga and widely cultured for its benefits. Pigments, lipid, and fatty acid compounds of Nannochloropsis sp are essential elements in the industry. This research aimed to determine the best light intensity on the growth rate, cell density and size, biomass, pigments (chlorophyll a, b, carotenoids), total lipid and fatty acid profile. Nannochloropsis sp. culture was carried out with three light intensity treatments (100, 155, and 180 μmol), with two replications. Periodicity was set up (16:8) with the ratio of dark (8h) to light (16h). The highest cell density and total pigment content of 180 μmol were significantly different (p<0.05) with 155 and 100 μmol. The highest weight of chlorophyll a, b, and carotenoids were found from the intensity of 180 treatment (p < 0.05), followed by 155 and 100 μmol as the smallest one. The bigger cell size was reached from 180 and 155 treatments compared to 100 μmol treatment. The higher wet weight was gained from 155 (564 grams) and followed by 180 μmol (549 grams). The 100 μmol light intensity produced the lowest wet weight (490 gr) (p<0.05). The highest total lipid content was obtained from 155 μmol treatment (0.14 g ww). The microalgae contain SFA/Saturated Fatty Acids (Palmitic, Stearic Acid) and UFA/Unsaturated Fatty Acid (Oleic Acid). The microalgae from 180 μmol produced Eicosanoic acid (Omega-6). The production of certain compounds has differed in light intensity. In the future, the light intensity can be adapted as the alternative solution for producing microalgae for industrial approach, whether for pigments or biodiesel production.